Predicting Factors for Retailers' Sale of Cigarettes to Adolescents in the Lower Part of Northern Region of Thailand - Phetphum, Chakkraphan; Wangwonsin, Artittaya; Noosorn, Narongsak (Journal of research in health sciences, 2017)
Thailand is one of the members of WHO FCTC and has paid so much attention to preventing adolescents' access to tobacco. However, Thai adolescents still have access to tobacco with ease. The aim of this research was to investigate the predicting factors for the cigarettes sale to adolescents by the retailers in Thailand. A cross-sectional study. This cross sectional survey was conducted after a careful desk review of the relevant literature. Multistage random sampling technique was used to sample the survey participants (n = 675) who were retailers of tobacco in the lower northern region of Thailand. Data were collected by validated questionnaires and analyzed by descriptive analytic, chi-square test and binary logistic regression. More than half (58.7%) of the participants sell cigarettes to adolescents. Factors such as open display of cigarette at the point of sale, selling cigarettes in sticks, selling cigarettes by self-service, and reluctant disregard of buyers' age by the seller significantly correlated with and predicted, at 95% level of confidence, the behavior of retailers selling cigarettes to adolescents. Thai adolescent's access to tobacco continues to be a serious public health problem. Therefore, the Ministry of Public Health and other relevant stakeholders saddled with the responsibility of interventions to scale up measures that would reinforce the law of Tobacco Control Act.